Ecology versus Property Rights: Land in the Capitalist World-Economy - Wallerstein, Immanuel (2014)
Access, ownership, and land use for agricultural and living purposes have undergone major changes over time, particularly with the emergence of the capitalist World-Economy. The present text offers a reflection on the propositions of property rights, as well as on the forms of gaining that right, ranging from land seizure, conquest, or “land development”. In the context of the capitalist World-Economy, the process of legitimization by means of right to legal ownership is a fundamental process. However, the emergence of social, libertarian, and resistance movements opposing restrictive property rights has had significant cultural, political, and economic impacts, in addition to major ecological consequences. This article offers several examples of the above, with special mention to the important social movements that have arisen in countries of the global south, and to the natural resources where impact is mostly felt.